Aging Is Accompanied by a Blunted Muscle Protein Synthetic Response to Protein Ingestion - Wall, Benjamin Toby; Gorissen, Stefan H.; Pennings, Bart; Koopman, René; Groen, Bart B. L.; Verdijk, Lex B.; van Loon, Luc J. C. (PloS one, 2015)
Progressive loss of skeletal muscle mass with aging (sarcopenia) forms a global health concern. It has been suggested that an impaired capacity to increase muscle protein synthesis rates in response to protein intake is a key contributor to sarcopenia. We assessed whether differences in post-absorptive and/or post-prandial muscle protein synthesis rates exist between large cohorts of healthy young and older men. We performed a cross-sectional, retrospective study comparing in vivo post-absorptive muscle protein synthesis rates determined with stable isotope methodologies between 34 healthy young (22±1 y) and 72 older (75±1 y) men, and post-prandial muscle protein synthesis rates between 35 healthy young (22±1 y) and 40 older (74±1 y) men. Post-absorptive muscle protein synthesis rates did not differ significantly between the young and older group. Post-prandial muscle protein synthesis rates were 16% lower in the older subjects when compared with the young. Muscle protein synthesis rates were >3 fold more responsive to dietary protein ingestion in the young. Irrespective of age, there was a strong negative correlation between post-absorptive muscle protein synthesis rates and the increase in muscle protein synthesis rate following protein ingestion. Aging is associated with the development of muscle anabolic inflexibility which represents a key physiological mechanism underpinning sarcopenia.